From adversity to achievement: Challenges, coping strategies, and performance outcomes of university faculty and staff in sports activities - Fadare, Stephen Ayoade; Adlawan, Hendely Arreza; Gumanoy, Dina Arquiola; Pagdato, Jonathan Vagilidad; Malinis, Amor Bedina (Journal of Interdisciplinary Studies in Education, 2026)
Faculty and staff participation in university sports may contribute to well-being, motivation, and sustained workplace engagement, yet their lived experiences in competitive institutional sports remain underexamined. This study explored how faculty and staff made sense of their participation in university sports activities, focusing on the challenges they encountered, the coping strategies they developed, and the factors they believed shaped their competitive performance. Using interpretative phenomenological analysis, semi-structured interviews were conducted with 12 purposely selected participants from a government public university in Mindanao. The analysis indicated that performance was shaped by fitness culture, prior sports progression, institutional adversities, as well as adaptive preparation strategies, self-fulfillment, and faculty and staff-management partnership. Despite institutional scarcity, participants described achieving strong performance through disciplined preparation, resilience, intrinsic motivation, and organizational support. The findings suggest that higher education institutions should strengthen equitable and sustainable sports programs for faculty and staff and recognize sports participation as part of employee development and institutional well-being.